Synthesis, molecular docking, and biological evaluation of 5‐alkyl(aryl)‐2‐isobutylthiazole derivatives: As α‐amylase, α‐glucosidase, and protein kinase inhibitors. (7th March 2022) - Khan, Siraj; Buğday, Nesrin; Rehman, Asim Ur; Haq, Ihsan Ul; Yaşar, Sedat; Özdemir, İsmail
Abstract: A series of 18 biologically active C5‐arylated‐2‐isobutylthiazole derivatives that were synthesized by Pd‐NHC complexes [Pd(μ‐Cl)Cl (NHC)]2, NHC = SIXyl, 2 ), (LCl2 Pd‐NHC, L = PPh3, 3 ), (LCl2 Pd‐NHC, L = Py, 4 ), (LCl2 Pd‐NHC, L = 3‐CHO‐Py, 5 ) catalyzed C‐H bond activation reactions. The catalytic activity of Pd‐NHC complexes was examined on the C‐H bond activation reaction of 2‐isobutylthiazole. All Pd‐NHC complexes were characterized by 1 H nuclear magnetic resonance specroscopy (NMR), 13 C NMR, fouirer transform infrared spektroscopy (FTIR), quadrupole‐time of flying‐liquit cromotagraphy/mass spektroscopy (Q‐TOF‐LC/MS), gas chromatography–mass spectrometry (GCMS), and melting point detection technique. The physicochemical properties, pharmacokinetics, and drug‐likeness were calculated by SwissADME. PkCSM database was used to calculate toxicities profile. All the products (6a–6s) were additionally assessed in vitro for their antidiabetic potential using α‐amylase and α‐glucosidase inhibitory activities. The protein kinase activity was performed to evaluate their anticancer activities. All the compounds possess drug‐like characters as they followed Lipinski's rule of five (RO5). Almost all the compounds showed no to fewer toxicities. In addition, other than the compounds, that is, 6a, 6b, 6c, 6m, 6n, 6p, and 6s, the rest of the compounds showed good α‐glucosidase inhibitory potential (IC50 7.17 ± 0.201 to 74.08 ± 0.244 μg/ml) when compared with acarbose standard (IC50 16.59 ± 0.135 μg/ml). All compounds had moderate to good inhibitory potential against the α‐amylase enzyme, with IC50 values ranging from 12.00 ± 0.289 to 76.15 ± 0.477 μg/ml. Eleven analogs (6e, 6f, 6g, 6h, 6j, 6k, 6l, 6n, 6o, 6p, and 6r) showed good to moderate activity. Seven analogs (6a, 6b, 6c, 6d, 6i, 6m, and 6s) showed no α‐amylase inhibitory activity. The protein kinase inhibition potential was determined for the first time, and the compounds 6d, 6e, 6f, 6h, 6k, 6p, and 6r depicted activity with the zone of inhibition in the range of 9 ± 1.3 to 19 ± 1.5 mm. The ligands and active site binding interactions of α‐glucosidase, α‐amylase, and protein kinase enzymes were also studied using molecular modeling. Abstract : 5‐Alkyl (aryl)‐2‐isobutylthiazole derivatives were assessed in vitro antidiabetic potential using α‐amylase and α‐glucosidase inhibitory activities. The protein kinase activity was performed to evaluate their anticancer activities. All the compounds possess drug‐like characters as they followed Lipinski's rule of five (RO5).